Pemilihan Sifat-Sifat Kg Sebagai Bahan Kkg Untuk Kemasan Produk B3 Golongan II - Budi Utami (Jurnal Kimia dan Kemasan, 2000)
Corrugated boxes as a transport packaging can reduce the damage of the contents during transportation. The packaging should conform with the design type and should be completely tested in accordance with the requirements of the UN Standard. Experiment has been carried out to determine the specification of fibreboard sheet which is used for corrugated boxes for group II dangerous goods. The type of corrugated boxes is Regular Slotted Container (RSC) with inner dimension 457 x 314 x 290 mm and 20 kg by weight.The transport: simulation test of corrugated boxes showed that the optimum physical properties of fibreboard were double wall, flute CIB , total gramage 850 g!nl , burshting strenght 12, 12 kg[/ cm2 and compression strength 4,39 kN/m.